Korelasi Type LRB Terhadap Penggunaan Di Struktur Elevated Guna Menghasilkan Efektifitas Hasil Penulangan Di Pier - Muhammad Nasir; Pio Ranap Tua Naibaho (Jurnal Konstruksi, 2026)
In the design of elevated bridge structures, the selection of Lead Rubber Bearing (LRB) types plays an important role in controlling seismic response and improving the efficiency of reinforcement requirements in piers. This study aims to analyze the correlation between variations in LRB specifications and the effectiveness of reinforcement in elevated pier structures. The methods used include literature study, three-dimensional numerical modeling, and structural response analysis using SAP2000 software with response spectrum and time-history approaches. The analysis results show that variations in LRB parameters, particularly effective stiffness (Keff) ranging from 0.60 to 0.81 kN/mm and characteristic strength (Qd) ranging from 39 to 80 kN, have a significant influence on the distribution of internal forces within the structure. The use of LRB with lower Keff values was able to reduce internal forces in the piers by approximately ±15–30 percent and significantly decrease longitudinal reinforcement requirements compared to configurations with higher stiffness. In addition, the LRB deformation capacity of 110–140 mm proved effective in enhancing seismic energy dissipation and maintaining the structural capacity-to-demand ratio close to the optimum condition of < 1.0. The contribution of this study demonstrates that optimizing LRB parameters, particularly Keff, can be used as a design strategy to produce pier structures that are more efficient, safe, and economical. These findings provide a technical basis for selecting appropriate seismic isolators to improve the performance of elevated structures under earthquake loads.